Synthesis of Some Aryl Ketoxime Derivatives with their in vitro Anti-microbial and Cytotoxic Activity - Oguzhan Karaosmanoglu; Burcu Butun; Hakan Dal; Hulya Sivas; Kadriye Benkli (Global Journal of Cancer Therapy - Peertechz Publications, 2019)
Benzofuwran derivatives found in several natural compounds and synthesized for various purposes. Due to their molecular structure's electron behaviors they have several biological activities such as antitumor, cytotoxic, anticancer, antimicrobial, antifungal, ant proliferative etc. We synthesized (3-methyl-benzofuran-2-yl) ketoxime derivatives (one of them are new compound) and structure elucidation of the compounds was performed using IR, 1H-NMR, MASS spectroscopy and elemental analysis. X-Ray analysis of H2 compound was elucidated for the first time with this study in the literature. Cytotoxic activity against F2408 and HepG2 cell lines was also evaluated for the first time by MTT and NR uptake methods. Anti-microbial activity of H1, H2 and H3 was also investigated with broth micro dilution test. The results show that these ketoximes have cytotoxic and anti-microbial activity on different higher doses.